Only you can save mankind / 1. - Pratchett, Terry., 1948-2015 (Pratchett, Terry. Johnny Maxwell trilogy, 2005)
Twelve-year-old Johnny endures tensions between his parents, watches television coverage of the Gulf War, and plays a computer game called Only You Can Save Mankind, in which he is increasingly drawn into the reality of the alien ScreeWee.